Voters' Political Participation in the Covid-19 Pandemic According to the Geography and Topography Condition of the Region (Study on the 2020 Regional Head Election in Pekalongan Regency) - Tri Lestari Hadiati; Haryanto Nugroho; Darmawan Tri Budi Utomo (Jurnal Politik Indonesia: Indonesian Political Science Review, 2022)
Implementation Election Regent and Representative Regent Pekalongan It is the year 2020, which is one of the elections in Indonesia, which was held amid the Covid-19 Pandemic, experiencing enhanced political participation in society. Different from the most significant challenge during this implementation election common in the district of Pekalongan is the level of participation people tends to be low because of the condition of geography and topography different in the district Pekalongan. The results of this study conclude that first, with the high political participation of voters during the COVID-19 pandemic, the opportunity for people to come to the polling station is significant. However, the topography and geography of the region also have a significant influence because each region provides equal opportunities for voters to come to the polling station. Second, implementing the 2020 Pekalongan Regent and Deputy Regent Elections can be carried out safely and adequately with high voter political participation. High voter political participation was achieved by 77.75% and exceeded the national target. That is equal to 77.50%. So it is also higher than in the previous elections. The findings show that the local government of Pekalongan Regency is more innovative in increasing the political participation of its people.